Sistematik Literatur Review Eksplorasi dan Identifikasi Karakteristik Padi Lokal Sumatra Barat - Zulkarnaini Zulkarnaini; Irfan Suliansyah; Gusmini Gusmini; Syafrimen Yasin (Lembaga Intelektual Muda (LIM) Maluku, 2024)
As much as 75% of people's daily calorie input in Asian countries comes from rice One of the provinces that has great potential as a contributor to national rice production is West Sumatra. Supported by natural resources and good climatic conditions and a large population, which is 4,846,909 people. The purpose of this article is to find out the development and mapping of research topics on Exploration and Identification of Local Rice Characteristics of West Sumatra. The type of research used is literature review using bibliometric analysis. The bibliometric analysis in this study shows a study of the evolutionary process on the research topic with local West Sumatran rice from 2010 to 2023. Vosviewer is an important programming tool for visualizing and analyzing network visualizations in mapping bibliometric analysis. Around 235 articles obtained from the Google Scholar database show that there is a use of the term West Sumatran local rice and can be a topic of future research.